Low penetrance genetic polymorphisms as potential biomarkers for colorectal cancer predisposition. (9th March 2018) - Tan, Shing Cheng
Abstract: Colorectal cancer is a leading form of cancer in both males and females. Early detection of individuals at risk of colorectal cancer allows proper treatment and management of the disease to be implemented, which can potentially reduce the burden of colorectal cancer incidence, morbidity and mortality. In recent years, the role of genetic susceptibility factors in mediating predisposition to colorectal cancer has become more and more apparent. Identification of high‐frequency, low‐penetrance genetic polymorphisms associated with the cancer has therefore emerged as an important approach which can potentially aid prediction of colorectal cancer risk. However, the overwhelming amount of genetic epidemiology data generated over the past decades has made it difficult for one to assimilate the information and determine the exact genetic polymorphisms that can potentially be used as biomarkers for colorectal cancer. This review comprehensively consolidates, based primarily on results from meta‐analyses, the recent progresses in the search of colorectal cancer‐associated genetic polymorphisms, and discusses the possible mechanisms involved.